In Vitro Determination of Antimicrobial and Hypoglycemic Activities of Mikania cordata (Asteraceae) Leaf Extracts - Pavithra L. Jayatilake; Helani Munasinghe (Biochemistry Research International)
Infectious diseases and diabetes mellitus are counted responsible for a substantial amount of mortality among the human population. The current study was performed to detect the antimicrobial activities and hypoglycemic potential of Mikania cordata (Asteraceae) leaves extracted into aqueous media and several organic solvents (ethyl acetate and methanol). The ethyl acetate extract of Mikania cordata (MEA) leaves was observed to possess significantly (p≤0.05) greater antimicrobial capabilities (susceptible against Bacillus cereus ATCC 11778 and Staphylococcus aureus ATCC 25923) when compared with that of the methanol (MME) and aqueous extracts (MDW) which were assessed based on Kirby-Bauer disk diffusion assay. The minimum inhibitory concentration of MEA (against B. cereus, S. aureus, and Escherichia coli ATCC 25922) and MME (against B. cereus, S. aureus, E. coli, and Candida albicans ATCC 10231) lies in a similar range of 1.13 > MIC>0.56 mg/ml. In the present study, a single compound (from MEA) of Rf value 0.64 was isolated by thin-layer chromatography (TLC) that was responsible for the zone of inhibition against B. cereus (20.3 ± 0.3 mm). The results of this study also depicted the antihyperglycemic properties of M. cordata leaves which followed the same trend as the commercial drug Metformin in a glucose concentration-independent manner when tested in a glucose uptake assay by yeast cells. Therefore, it is evident that Mikania cordata is a reservoir of useful bioactive compounds which with further research will be paving the path for drug commercialization. This is the first record of TLC-based isolation of antimicrobial compounds of M. cordata and analysis of the hypoglycemic properties of M. cordata leaves.